Screening for nasal carriage of methicillin resistance Staphylococcus spp. among housekeeping personnel in a tertiary care hospital - Mistry, Yogita; Mullan, Summaiya; Gondaliya, Nirav; Sarkar, Kristi; Kanani, Komal (International Journal Of Community Medicine And Public Health, 2025)
Background: Methicillin resistance Staphylococcus aureus and coagulase negative Staphylococci are commonly isolated pathogens from nosocomial infections. Colonized hospital personnel may be an important factor in dissemination of infection to patients and vice- versa. Among the various cadres of healthcare workers, housekeeping personnel are the most significant source of pathogen dissemination compared to other hospital staff, such as doctors, nurses, and lab technicians. This study aimed to determine the rate of methicillin-resistant Staphylococcus spp. colonization among housekeeping personnel at a tertiary care institute. Methods: This study was a prospective study. Approximately 150-200 Housekeeping personnel were working in Hospital setting at the time of study period. Those with upper respiratory tract infections and those with history of intake of antibiotics in previous 3 months were excluded. A single nasal swab was used to take the mucosal samples from both the anterior nares by the study investigators. Results: A total 40 housekeeping personnel had participated and agreed to give nasal samples. Out of 40 Housekeeping personnel nasal swab, 12 (30%) had shown gram positive cocci in clusters. Out of 12 isolates, only 1 (8%) isolate was Staphylococcus aureus, all other 11 (92%) isolates were Coagulase Negative Staphylococcus. Out of 11 Coagulase Negative Staphylococci, 4 (36%) were MRCoNs. And no MRSA found in housekeeping personnel. Conclusions: Colonized Housekeeping personnel may be an important factor in the dissemination of infection from them to patients and vice-versa. Policies and guidelines should be framed to create awareness among HCWs regarding the screening methods for the detection and treatment of nasal carriage.